Search
Ask a question
0

describe and correct error

 
how do I describe and correct this error:
 
   (3x - 2) (2x - 3)
 
  =3x(2x-3) - 2(2x - 3)
  =6x^2-9x-4x-6
  =6x^2-13x-6
 
Thank you

2 Answers by Expert Tutors

Tutors, sign in to answer this question.
Charles G. | Math, Biology, Engineering, Physics, Chemistry, and Business TutorMath, Biology, Engineering, Physics, Che...
1
(3x-2)(2x-3) = 6x^2-9x-4x+6 = 6x^2-13x+6
 
Your error is in multiplying -2*-3 = +6 not -6.
Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...
4.8 4.8 (4 lesson ratings) (4)
1
 The second line:
 
    - 2 ( 2X - 6 ) = -4X +6